STRATEGI INOVATIF DALAM MENUMBUHKAN IDENTITAS NASIONAL MELALUI PENDIDIKAN STUDI KASUS DI SMP NEGERI 19 KERINCI: STUDI KASUS DI SMP NEGERI 19 KERINCI - murlinus, murlinus; Agusta, Aras Satria (Universitas Negeri Surabaya (Unesa), 2024)
This study examines how the values of nationalism are instilled in students at SMP Negeri 19 Kerinci. The focus of the research includes the strategies used to foster those values, as well as the evaluations and constraints encountered during their application. Analyses were also conducted of the impact of such policies on students' attitudes and behavior, as well as their active participation in activities that reinforce nationalism in the school environment. The study uses a qualitative approach with an inductive framework, collecting data through interviews, observations, and document analysis, which are then processed through categorization, deduction, and inference. The results show that the cultivation of nationalism values is carried out through three main strategies in the integration of the values of nationalism into seven main subjects through special syllabus, habitus strategies and programmed activities, and the use of technology and performing arts as a medium of learning. Research identifies specific barriers such as differences in family environments and technology limitations, thus offering holistic educational policy-based solutions. The results of this study demonstrate the importance of collaboration between educators, policymakers, and the public to create a learning environment that supports the development of national identity among students.